Reduced survival of Steller sea lions in the Gulf of Alaska following marine heatwave - Kelly K. Hastings; Thomas S. Gelatt; John M. Maniscalco; Lauri A. Jemison; Rod Towell; Grey W. Pendleton; Devin S. Johnson (Frontiers in Marine Science, 2023)
The North Pacific marine heatwave of 2014–2016 (PMH), one of the most geographically-extensive and severe marine heatwaves on record, resulted in widespread and persistent perturbation of the Gulf of Alaska and California Current ecosystems. Negative effects of the PMH on marine mammals have been observed, but are not yet well understood. The endangered Steller sea lion Eumetopias jubatus is an important top predator in the Gulf of Alaska that is also particularly vulnerable to sudden or severe ecosystem shifts. We examined survival of 4,178 known-aged Steller sea lions marked from 2000 to 2016 from Kodiak Island through Southeast Alaska, using mark-recapture models and 12,811 resightings collected from 2001 to 2021. Survival of adult females aged 3–15 was reduced -0.05 to -0.23 during the PMH in the areas east, but not west, of Cook Inlet. Survival of Kodiak females was unaffected by the PMH, but survival of Sugarloaf females aged 5–8 was reduced -0.13 from summer 2015 to summer 2016. Lowest survival in Southeast Alaska occurred from summer 2016 to summer 2017, but was also reduced from summer 2014 to summer 2016. Reduced survival continued post-PMH in Kenai Peninsula/Prince William Sound, but not in Southeast Alaska. Survival of adult males was insensitive to the PMH, except in Southeast Alaska where male survival was reduced -0.25 from summer 2016 to summer 2017. Prolonged or intermittent high adult female mortality may reduce population growth and initiate regional declines. Survival response of Steller sea lions to the PMH varied regionally despite similar patterns of ocean warming throughout our study area, suggesting areas east versus west of Cook Inlet were affected differently by the PMH, perhaps due to habitat and oceanographic differences.

Short‐term survival of Steller sea lion ( Eumetopias jubatus ) pups: Investigating the effect of health status on survival - Grey W. Pendleton; Kelly K. Hastings; Lorrie D. Rea; Lauri A. Jemison; Greg M. O'Corry‐Crowe; Kimberlee B. Beckmen (Marine Mammal Science, 2016)
We estimated survival probabilities for Steller sea lion ( Eumetopias jubatus ) pups from 3 wk to 6 wk old and from 6 wk to 1 yr at three rookeries in southeastern Alaska. We also investigated the effect of mass, body condition, health variables, and the genetic origin on 3–6 wk survival. Survival differed substantially among rookeries and between sexes, with survival lowest at Hazy Islands, intermediate at White Sisters, and highest at Graves Rocks and survival lower for males than females. Body mass, body condition, and hematocrit were positively related to survival and blood %H 2 O and haptoglobin level (for females; no relationship for males) were negatively related to survival. Taking predictor variables collectively, sea lion pups at Hazy Islands, which had the lowest survival probability, had the lowest mass, hematocrit, and hemoglobin, and had high levels of blood %H 2 O, and hookworm infection. Values from Graves Rocks, which had the highest survival, were the opposite of those from Hazy Island ( e.g ., high mass, body condition, hematocrit, and hemoglobin), while those from White Sisters (intermediate survival) had varying means ( e.g ., high hematocrit and hemoglobin and low hookworms, but also low body condition); these patterns suggest that physiological factors potentially underlie rookery differences in survival.

Population growth and colonization of Steller sea lions in the Glacier Bay region of southeastern Alaska: 1970s–2009 - Elizabeth A. Mathews; Jamie N. Womble; Grey W. Pendleton; Lauri A. Jemison; John M. Maniscalco; Greg Streveler (Marine Mammal Science, 2011)
We estimated trends in numbers of Steller sea lions in the Glacier Bay region of the eastern population from the 1970s to 2009. We documented the colonization of several new haul‐outs and the transition of one haul‐out (Graves Rocks) to a rookery, assessed seasonal patterns in distribution, and compared counts from different observation platforms. Sea lions increased in the region by 8.2%/yr (95%CI = 6.4%–10.0%), with the most growth at South Marble Island in Glacier Bay (16.6%/yr, 1991–2009) and rapid growth in Cross Sound. Seasonal patterns in the distribution of sea lions were likely influenced by new breeding opportunities and the seasonal availability of prey. Factors that likely contributed to the exceptional growth include availability of new habitat following deglaciation, immigration, redistribution, decreases in mortality, and ecosystem‐level changes. The rapid increase in sea lion numbers in this region is of particular interest in light of dramatic declines in the western population and evidence that Steller sea lions from both the eastern and western populations colonized the Graves Rocks rookery. The colonization and rookery development in this dynamic area may signal the reversal of the reproductive isolation of the two populations.

Harbor seal ( Phoca vitulina richardii ) decline continues in the rapidly changing landscape of Glacier Bay National Park, Alaska 1992-2008 - Jamie N. Womble; Grey W. Pendleton; Elizabeth A. Mathews; Gail M. Blundell; Natalie M. Bool; Scott M. Gende (Marine Mammal Science, 2009)

Estimating age of harbor seals ( Phoca vitulina ) with incisor teeth and morphometrics - Gail M. Blundell; Grey W. Pendleton (Marine Mammal Science, 2008)
We compared annuli counts from sets of canine, postcanine, and incisor teeth from 450 subsistence‐harvested harbor seals, submitted blind to a laboratory. Postcanine and incisor ages were highly correlated with canine age estimates ( r = 0.985 and r = 0.984, respectively), as were postcanine and incisor teeth ( r = 0.984). Age estimates from teeth of 23 known‐aged seals were highly correlated; canine teeth r = 0.987; postcanine r = 0.996; incisor r = 0.992, although age for all tooth‐types was underestimated for a 29‐yr‐old seal. Incisor estimates were variable; comparison of age estimates from two incisors/individual ( n = 42) was r = 0.992 if only high‐quality age estimates were used and r = 0.705 if lower‐quality estimates were used. Morphometrics and incisor‐based ages of 164 live‐captured seals were explored to derive a method of estimating ages of harbor seals when age estimates are needed immediately; 39 seals were of known age. Curvilinear length, mass, and axial girth were most predictive of age for females, and curvilinear length and mass for males (equations for morphometrically calculating ages are given). Morphometric‐based age estimates were highly correlated with known ages ( r = 0.896) and incisor‐based estimates ( r = 0.904) and discrepancies between known and morphometric‐based ages were small for younger seals. Morphometric‐based age estimates also accurately distinguished between young and mature individuals.

A FIELD‐BASED METHOD FOR ESTIMATING AGE IN FREE‐RANGING STELLER SEA LIONS ( EUMETOPIAS JUBATUS ) LESS THAN TWENTY‐FOUR MONTHS OF AGE - James C. King; Thomas S. Gelatt; Kenneth W. Pitcher; Grey W. Pendleton (Marine Mammal Science, 2007)
Studies of health, survival, and development of juvenile Alaskan Steller sea lions ( Eumetopias jubatus , SSL) require accurate estimates of age for wild‐captured animals. However, the value and accuracy of several potential predictors of age have not been assessed with data from known‐age free‐ranging animals. During 2001–2005, forty‐six individual SSL originally branded or tagged at ≤6 mo of age were recaptured by the Alaska Department of Fish and Game (ADF&G). Using a series of general linear models, we evaluated the ability of morphometrics measurements: permanent canine tooth length (CTL), diastema (DIAS), whisker length (WHIS), and dorsal standard length (DSL) to predict the age of forty‐six known‐age juveniles ( n = 46 ≤23 mo of age). Permanent CTL was the strongest individual predictor ( r 2 = 0.80); followed by DSL, DIAS, and WHIS ( r 2 = 0.70, 0.56, and 0.45, respectively). The inclusion of a single sample from a 44‐mo‐old sea lion suggested quadratic relationships between age and all predictors for older animals. Only models including CTL predicted age to within 6 mo of known age. The equation Age = (−3.0112 +[0.6726 * CTL]+[0.4965 * DIAS]) allows for accurate age estimates of SSL ≤23 mo for both sexes.

LONG‐TERM TRENDS IN HARBOR SEAL NUMBERS AT TUGIDAK ISLAND AND NANVAK BAY, ALASKA - Lauri A. Jemison; Grey W. Pendleton; Carol A. Wilson; Robert J. Small (Marine Mammal Science, 2006)
We conducted land‐based counts of harbor seals ( Phoca vitulina richardii ) and collected related environmental data at Tugidak Island (Gulf of Alaska, 1994–2000) and Nanvak Bay (Bristol Bay, 1990–2000) to estimate population trends and identify factors influencing counts. At Tugidak Island, the seal population declined substantially during molting from 1976 through the 1980s, stabilized in the early 1990s, and increased at a moderate rate (3.4%/yr, CI: 1.0%–5.8%) from 1994 to 2000. Pups and all seals ashore during pupping increased at higher annual rates of 5.4% (CI: 2.2%–8.8%) and 8.3% (CI: 4.5%–12.3%) from 1994 to 2000 at Tugidak Island. At Nanvak Bay seals declined in abundance between 1975 and 1990 but increased during the 1990s at 9.2%/yr (CI: 7.2%–11.3%) during pupping and 2.1%/yr (CI: 0.6%–3.6%) during molting. Date and time‐of‐day were significant covariates in all analyses. Factors that led to declines at Tugidak Island and Nanvak Bay have seemingly abated sufficiently such that these populations are currently increasing, though still greatly reduced from the 1970s. Index sites are useful adjuncts to aerial surveys, providing survey‐related information not always available from aerial counts, which is useful in survey design and data analysis.

DECLINES IN HARBOR SEAL (PHOCA VITULINA) NUMBERS IN GLACIER BAY NATIONAL PARK, ALASKA, 1992–2002 - Elizabeth A. Mathews; Grey W. Pendleton (Marine Mammal Science, 2006)
Glacier Bay National Park had one of the largest breeding aggregations of harbor seals in Alaska, and it is functionally the only marine reserve for harbor seals in Alaska; yet, numbers of seals in the Bay are declining rapidly. Understanding why seals in Glacier Bay are declining may clarify their minimal habitat needs. We estimated population trends using models that controlled for environmental and observer‐related factors. In 1992, 6,200 seals were counted on icebergs in a tidewater glacial fjord and at terrestrial sites; by 2002 only 2,550 seals were counted at these same haul‐outs. Numbers of non‐pups in the glacial fjord declined by 6.6%/yr (−39%/8 yr) in June and by 9.6%/yr (−63%/11 yr) in August and at all other haul‐outs by 14.5%/yr (−75%/10 yr) during August. In the glacial fjord the number of pups remained steady from 1994 to 1999 and made up an increasing proportion of seals counted (5.4%/yr), and the proportion of pups peaked at 34%–36%. The rapid declines do not appear to be due to changes in seal behavior or redistribution. The declines reinforce genetic evidence that harbor seals in Glacier Bay are demographically isolated from other populations and indicate that current management stocks need to be redefined. Changes in Glacier Bay's ecosystem and population demographic data from the glacial fjord suggest that interspecific competition and predation are likely factors in the declines.

DEVELOPMENT OF DISPERSAL, MOVEMENT PATTERNS, AND HAUL‐OUT USE BY PUP AND JUVENILE STELLER SEA LIONS ( EUMETOPIAS JUBATUS ) IN ALASKA - Kimberly L. Raum‐Suryan; Michael J. Rehberg; Grey W. Pendleton; Kenneth W. Pitcher; Thomas S. Gelatt (Marine Mammal Science, 2004)
A bstract Population declines of Steller sea lions ( Eumetopias juhatus ) in western Alaska (west of 144°W) may be a result of reduced juvenile survival. We used satellite telemetry to study the at‐sea distribution and movement patterns of pup (1.6–11.9 mo) and juvenile (12.0–35.1 mo) Steller sea lions. We studied trip distance, duration, and interhaul‐out movements of sea lions in relation to age, sex, and month of year in the decreasing western population (WP; Prince William Sound, Kodiak, Aleutian Islands, Alaska) and the increasing eastern population (EP; Southeast Alaska). We deployed 103 satellite transmitters (29 WP; 74 EP) on sea lions between 1998 and 2001. Round trip distance and duration increased with age, trip distance was greater in the WP than the EP, trip duration was greater for females than males, and haul‐out use was clustered. Changes in round trip distance and duration occurred from April to June for all age classes studied indicating that the annual timing of weaning may be less variable than the age of weaning. Overall, 90% of round trips were ≤ 15 km from haul‐outs and 84% were

TRENDS IN ABUNDANCE OF ALASKA HARBOR SEALS, 1983–2001 - Robert J. Small; Grey W. Pendleton; Kenneth W. Pitcher (Marine Mammal Science, 2003)
A bstract We estimated trends in abundance of harbor seals ( Phoca vitulina richardsii ) using over dispersed, multinomial models and counts obtained during aerial surveys conducted during 1983–2001 in the Ketchikan, Sitka, Kodiak, and Bristol Bay areas of Alaska. Harbor seal numbers increased significantly at 7.4%/yr during 1983–1998 and 5.6%/yr during 1994–1998 in the Ketchikan area, and 6.6%/yr during 1993–2001 in the Kodiak area. Counts were stable (trends not significant) during 1984–2001 (0.7%/yr) and 1995–2001 (‐0.4%/yr) in Sitka, and during 1998–2001 (‐1.3%/yr) in Bristol Bay. The influence of covariates ( e.g. , survey date, tide height) on trend estimates was significant and varied among areas and across years, demonstrating the need to include covariates in statistical analyses to accurately estimate trend. Our increasing trend estimate for Kodiak represents the first documented increase in harbor seal numbers over a relatively expansive area in the Gulf of Alaska. However, the trend for the Gulf of Alaska stock is equivocal due to the continued decline in Prince William Sound. Similarly, the trend for the Southeast Alaska stock is equivocal based on our increasing (Ketchikan) and stable (Sitka) trend estimates, and a recent decline reported for Glacier Bay. The Bering Sea stock appears stable after a period of possible decline.

MOLTING PHENOLOGY OF HARBOR SEALS ON TUGIDAK ISLAND, ALASKA - Raychelle G. Daniel; Lauri A. Jemison; Grey W. Pendleton; Shannon M. Crowley (Marine Mammal Science, 2003)
A bstract We documented the progression and timing of the annual molt of harbor seals on Tugidak Island, Alaska, from 1997 to 1999. In all years the timing of molting differed among age‐sex classes. Yearlings molted first, subadults second, adult females third, and lastly adult males. Timing of molting was nearly identical in 1997–1998, whereas in 1999 molting occurred three to six days later for all age‐sex classes except yearlings. Estimated dates when peak proportions of each age‐sex class were molting ranged from 2 August (yearlings) to 2 September (adult males). The number of seals hauled out was positively related to the proportion of seals in the molt and negatively related to the proportion of seals in the postmolt. Population trend estimates, based on aerial counts conducted during a narrow window within the molting period, are likely biased toward certain age‐sex classes. Statistical models used to estimate trend include covariates to help account for within‐year variation in seal numbers, but do not account for compositional changes that occur during molting. Population modeling may elucidate the effects of within‐year population structure on trend estimates. Monitoring molting phenology at additional sites is necessary to determine the extent of geographic variation in molting.

Interactive effects of selenium, methionine, and dietary protein on survival, growth, and physiology in mallard ducklings - David J. Hoffman; Caroline J. Sanderson; Leonard J. LeCaptain; Eugene Cromartie; Grey W. Pendleton (Archives of Environmental Contamination and Toxicology, 1992)

Interactive effects of arsenate, selenium, and dietary protein on survival, growth, and physiology in mallard ducklings - David J. Hoffman; Caroline J. Sanderson; Leonard J. LeCaptain; Eugene Cromartie; Grey W. Pendleton (Archives of Environmental Contamination and Toxicology, 1992)

Interactive effects of boron, selenium, and dietary protein on survival, growth, and physiology in mallard ducklings - David J. Hoffman; Caroline J. Sanderson; Leonard J. LeCaptain; Eugene Cromartie; Grey W. Pendleton (Archives of Environmental Contamination and Toxicology, 1991)

Selenium accumulation and elimination in mallards - Gary H. Heinz; Grey W. Pendleton; Alexander J. Krynitsky; Lyn G. Gold (Archives of Environmental Contamination and Toxicology, 1990)